Combined wave and surge overtopping erosion failure model of HPTRM levees: Accounting for grass-mat strength. (15th November 2015) - Yuan, Saiyu; Tang, Hongwu; Li, Lin; Pan, Yi; Amini, Farshad
Abstract: High performance turf reinforcement mat (HPTRM) has emerged as an effective and flexible strengthening system to protect earthen levees against the erosion caused by overtopping flows. The purpose of this study is to characterize the erosion and failure processes of HPTRM-strengthened levees under combined wave and surge overtopping. The Erosion Function Apparatus (EFA) is used to analyze the erodibility of HPTRM-strengthened clay. The erodibility parameters such as critical shear stress and erodibility coefficient are then obtained. A HPTRM-element model is proposed to account for the mechanism of HPTRM in protecting cohesive soil with the help of EFA results in the characterization of the grass mat strength parameter. At last, a failure model is developed based on the excess stress equation, and the durations of HPTRM-strengthened levees against combined overtopping with different wave heights and freeboards are presented. Highlights: We use EFA to analyze the erodibility of clay with or without protections. We obtain the erodibility parameters such as critical shear stress and erodibility coefficient. A HPTRM-element model is proposed for the protection mechanism of HPTRM. A failure model for HPTRM-strengthened levee against the combined overtopping is developed. The durations of HPTRM-strengthened levees against combined overtopping are presented.